Coincidence point theorems for multi-valued mappings of reich-type on metric spaces endowed with a graph - Tiammee,J. (Yokohama Publishers, 2015)
© 2015. In this paper, we introduce the concepts of G-contraction multi- valued mappings of Reich-type on a metric space endowed with a directed graph G. Some coincidence point theorems for this type of multi-valued mapping and a surjective mapping g: X → X under some properties on X and some contractive conditions of Reich-type are established. Some examples of mappings of this type and some examples satisfying all conditions of our main theorems are also given. Our main results extend and generalize many coincidence point and fixed point theorems in partially ordered metric spaces in the literature.